PENINGKATAN HASIL BELAJAR DALAM PEMBELAJARAN BIOLOGI MELALUI PENERAPAN STRATEGI SURVEY, QUESTION, READ, RECITE, AND REVIEW (SQ3R) PADA SISWA KELAS XI IPA 2 SMA NEGERI 1 BANYUDONO TAHUN AJARAN 2011/2012 - Palupi, VA Vellariani Dewi; Santosa, Slamet; Probosari, Riezky Maya (Pendidikan Biologi, 2012)
ABSTRACT ? This  research aimed for  improving studentachievementin learning process on Biology by implementation of  Survey, Question, Read, Recite, and Review  (SQ3R) strategy of  grade XI  IPA  2 SMA Negeri 1 Banyudono academic years 2011 / 2012.  This research is aclassroom  action research that was included 2 cycles of action. Each cycles consisting of 4 phase which areplanning, action, observation, and reflection. The subjects of this research were students grade XI IPA 2 SMA Negeri 1 Banyudonoacademic years 2011  / 2012.  Source  of  data  derived  from  the questionnaire, observation,  test  and interview. Technical analysis of data was using descriptive analysis. Data validation was using methods triangulation. The results of this research showed that the implementation  Survey, Question, Read, Recite, and Review  (SQ3R)  strategy  could improve  student achievement  in learning process on Biology  of  grade XI IPA 2 SMA Negeri 1 Banyudonoacademic years 2011 / 2012.  The  average  percentage based on questionnaire  student  achievement of  psychomotorindicators was  75,49% forCycle Iand  80,02%  forCycle II(worked up  4,53%).  The average  percentage based on  questionnaire  student  achievement of  affective  indicators was  69,48% forCycle Iand  78,09%  forCycle II  (worked up  8,61%).  The average  percentage based on observation student achievement of psychomotor  indicators for Cycle I was 57,81% and 67,60% forCycle II (worked up 9,79%). The average percentage based on observation student achievement of affective   indicators for Cycle I was 55,35% and  63,76%  forCycle II  (worked up  8,41%).  The average  percentage student  achievement of cognitivebased on evaluation test  for Cycle I  was 74,84and   85,63for Cycle II (worked up   10,79).Based on the result could be conclude that  implementation  of  Survey, Question, Read, Recite, and Review (SQ3R)  strategy  had improvedstudent achievement  in learning process on Biologyof grade XI IPA 2 SMA Negeri 1 Banyudono. Keywords:  Survey, Question, Read, Recite, and Review (SQ3R),  Psychomotor, Affective, Cognitive,and Students Achievement